2019
DOI: 10.1021/acs.jafc.9b01443
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromone of the Invasive Mealybug Citrus Pest, Delottococcus aberiae (Hemiptera: Pseudococcidae). A New Monoterpenoid with a Necrodane Skeleton

Abstract: Native to sub-Saharan Africa, Delottococcus aberiae De Lotto (Hemiptera: Pseudoccidae) is an invasive mealybug that has been recently reported in Europe seriously damaging citrus production in eastern Spain. In this study, we isolated and determined the structure of the sex pheromone of D. aberiae, to provide a highly specific and effective lure for detecting, monitoring and potentially controlling this pest. The volatile profile of D. aberiae virgin and mated females was studied by aeration and collection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…Sex pheromones comprise sex attractant pheromones, which induce upwind oriented movements to the conspecific individual, and courtship pheromones, which elicit a variety of close-range responses in the insect partner [ 12 , 13 ]. Since the first pheromone discovery, the rapid progress of methodologies developed to identify new pheromones, mainly GC, GC-MS, NMR, electrophysiological techniques [electroantennography (EAG), gas chromatography coupled to electroantennography (GC-EAD), single sensillum recordings (SSR), and coupled GC-SSR], have allowed the identification of thousands of compounds as insect sex pheromones [ 14 ] ( Table 2 contains new sex pheromones and sex pheromone components recently identified from insect pests in the period 2010–2020 and the corresponding references [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]). In addition, an interdisciplinary approach involving advances in analytical chemistry, neurophysiology, genetics, and molecular biology have improved our understanding of insect chemical communication and behavior to the level of discrete neural circuits [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sex pheromones comprise sex attractant pheromones, which induce upwind oriented movements to the conspecific individual, and courtship pheromones, which elicit a variety of close-range responses in the insect partner [ 12 , 13 ]. Since the first pheromone discovery, the rapid progress of methodologies developed to identify new pheromones, mainly GC, GC-MS, NMR, electrophysiological techniques [electroantennography (EAG), gas chromatography coupled to electroantennography (GC-EAD), single sensillum recordings (SSR), and coupled GC-SSR], have allowed the identification of thousands of compounds as insect sex pheromones [ 14 ] ( Table 2 contains new sex pheromones and sex pheromone components recently identified from insect pests in the period 2010–2020 and the corresponding references [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]). In addition, an interdisciplinary approach involving advances in analytical chemistry, neurophysiology, genetics, and molecular biology have improved our understanding of insect chemical communication and behavior to the level of discrete neural circuits [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unnatural stereoisomers in general have no biological activity or are slightly active (Einhorn et al 1990;Zhang et al 2004;Millar et al 2012;Tabata et al 2017a; and their presence in the mixture does not negatively affect the biological activity of the pheromone. Thus, in many cases it is not necessary to remove the opposite enantiomer generated during pheromone synthesis to be employed in pest management programs and racemates are perfectly active (Hinkens et al 2001;Zada et al 2003;El-Sayed et al 2010;Vacas et al 2019), which is economically favourable for their implementation. Possible inhibitory effects were reported in a rather few cases: the (S)isomer of solanone might be responsible for the weak activity of the racemic solanone in the field for Aulacaspis murrayae Takahashi (Ho et al 2014).…”
Section: Major Patterns In Scale Sex Pheromone Structuresmentioning
confidence: 99%
“…The classical methods employed since the 1970s for the isolation and identification of sex pheromones consist mainly of volatile collection and chromatographic techniques. For this purpose, an abundant supply of insects is needed because virgin females of scale species release smaller amounts of pheromone, i.e., 0.2-10 ng/day (Levi- Zada et al 2014;Tabata & Ichiki 2015;Vacas et al 2019) and 75 ng/day as the maximum reported (Tabata et al 2012), than female moths, which release 0.3-25 ng/h (Lacey & Sanders 1992;Anfora et al 2005). This implies that tens of thousands (Zada et al 2003) and even hundreds of millions (Roelofs et al 1977) of female-day equivalents (quantity of pheromone collected from one female each day) have to be sampled to obtain enough crude quantity that allows isolation of the target compound and the employment of spectroscopic techniques for its identification.…”
Section: Techniques For Isolation and Identification Of Scale Sex Phe...mentioning
confidence: 99%
“…In 2019, (2,2,3,4-tetramethylcyclopent-3-ene-1-yl)­methanol (γ-necrodol) and γ-necrodyl isobutyrate were found to be released by females of the spherical mealybug N. viridis, while (4,5,5-trimethyl-3-methylenecyclopent-1-en-1-yl)­methyl acetate (β-necrod-1-en-1-yl methyl acetate) (Figure ), with an unusual β-necrodol skeleton, was found in Delottococcus aberiae (De Lotto) (Hemiptera: Pseudococcidae) . α-Necrodols and their acetate derivatives were also found in two other plant species: Lavandula luisieri (Rozeira) Riv.…”
Section: Introductionmentioning
confidence: 99%